TWO DECADES OF GEOGRAPHICAL HIGHER EDUCATION IN BAIA MARE (1998-2018) - TOFAN, George-Bogdan (Studia Universitatis Babeș-Bolyai Geographia, 2019)
This paper aims to emphasize the history of the geographical tertiary education system in the Baia Mare Municipality (1998-2018), looking into „the transformations” of the Geography specialisation, specifically the evolution of enrolled students and graduates, the annual staff dynamics, as well as a synthesis of its educational and scientific achievements, ending with a presentation of its infrastructure. The 1998-1999 academic year corresponds with the accreditation of the first two specialisations of the Baia Mare Branch, one of them being History-Geography, long-term studies (4 years) in Romanian, part of the Faculty of Human-Christian Sciences, from „Vasile Goldiș” University Arad. The purpose of said specialisation was to provide competent teachers for the schools of Maramureș and the surrounding counties, preparing seven series of graduates (25 in 2002 and 40 in 2008), a total number of 601 students, reaching its peak (126) in 2004-2005. The fall of 2005 is the first significant moment in the history of Baia Mare Geography, as the Faculty of Natural Sciences was established and the History-Geography specialisation was transformed into the Geography Section, short-term day studies (3 years). It did not last long however, having only one series of graduates (12 in 2008 of a total of 18 enrolled students in 2005-2006). A year later, a new change occured, when a new specialisation was established, named Geography of Tourism, still operating to this day. In its 12 years of existence, it was first part of the Faculty of Nature Sciences, Engineering and Informatics (2011), Biology, Ecology and Geography Department, then part of the Faculty of Economic Sciences, Informatics and Engineering, without its own departament. It is currently part of the Engineering and Informatics Department. Of the total 1,770 students, who studied one of the three geographical specialisations during 1998-2018, the number of graduates (between 2002-2018) was 447 (25.2%), 256 studying Geography of Tourism (57.2%), 179 History-Geography (40%) and 12 Geography (2.8%). In terms of length, long-term studies (History-Geography) holds 44.8% (793 students) of the 1,770 students, while short-term studies (Geography, Geography of Tourism) reaches 55.2% (977 students, 43 at Geography and 934 at Geography of Tourism). The second major component that the paper aims to present is the educational and scientific staff, by carefully presenting the achievements for each member of „Vasile Goldiș” University of Arad.